Rhinocerebral and rhinopharyngeal conidiobolomycosis in sheep - Câmara,Antônio Carlos Lopes (2011)
The present study aimed to report the occurrence as well as the clinical, laboratorial, pathological and mycological findings of three outbreaks of rhinocerebral and rhinopharyngeal conidiobolomycosis in sheep from Rio Grande do Norte state, Brazil. A total of six sheep with clinical signs of conidiobolomycosis were evaluated, and information on history was obtained from ranchers. Clinical signs included depression, progressive emaciation, sero-sanguinolent nasal discharge, tachycardia, dyspnea, miosis and unilateral exophthalmia with increased ocular globe volume, corneal ulceration and nervous system signs. The main hematological alteration was neutrophilia. Serum biochemical evaluation revealed increased values for AST, GGT, creatinine, urea, and glucose, and decreased total proteins and albumin levels. Cerebrospinal fluid analysis showed the presence of fibrin reticules and pleocytosis. Upon necropsy, longitudinal sections of the head revealed the presence of a nodular mass with a friable consistency and a white-yellowish coloration. Microscopic findings included meningitis, cortex necrosis and encephalitis with the presence of eosinophilic Splendore-Hoeppli substance. Histopathology of the lungs revealed a Splendore-Hoeppli-like material and hyperplasia of alveolar and bronchiolar epithelium. Renal lesions were suggestive of amyloidosis.